IMPROVING THE METHODOLOGY FOR DEVELOPING PRAGMATIC COMPETENCE IN TEACHING ENGLISH TO MEDICAL STUDENTS - Atamuratova Munira Makhamadievna (Web of Journals Publishing, 2025)
This article analyzes the issues of forming and developing pragmatic competence in the process of English language education among medical students. The author outlines the theoretical foundations of pragmatic competence, existing problems and methodological solutions. According to the results of the study, it was proven that when using a communicative approach, tasks based on empathy, cross-cultural comparison and innovative technologies, positive changes were observed in the speech activity of students.
Keywords: Pragmatic competence, medical students, English, empathy, communicative methodology, intercultural communication.